ANALYSIS OF THE INFLUENCE OF LEADERSHIP AND WORK MOTIVATION OF OFFICIALS ON THE QUALITY OF HEALTH SERVICES FOR HEALTHY INDONESIA CARD USERS IN DEPOK CITY - Ismaniah Ismaniah; Tyastuti Sri Lestari; Agus Hidayat (JURNAL DARMA AGUNG, 2023)
This research is motivated by service problems for Healthy Indonesia Card users in Depok City. Service quality problems are thought to be caused by ineffective leadership and low employee motivation. This research only focused on the variables of leadership, work motivation and service quality. This study aims to determine the effect of leadership and work motivation on service quality for Healthy Indonesia Card users in Depok City, either partially or collectively. The sampling technique in this study was proportional stratified random sampling with a total sample of 286 respondents. This research method is a quantitative method with regression analysis. Data collection techniques using documentation, questionnaires and literature study. Research data collection tool is a questionnaire based on a Likert scale. The data analysis technique uses simple and multiple linear regression analysis. The results prove that leadership and work motivation are proven positive and significant to service quality partially or collectively.